Challenges and Survival Strategies of People Dislocated due to Tana Beles Integrated Sugar Factory: The Case of Bambajihua Relocation Site, Benishangul Gumuz Region - Aynalem, Seblewongiel; Muket, Asfaw (Ethiopian Journal of Social Sciences, 2018)
Development-induced dislocation could be an opportunity or a challenge for the dislocated people as well as the host community. This study was conducted to examine the challenges and survival strategies of people dislocated due to Tana Beles Integrated Sugar Factory (TBISF) project at Bambajihua relocation site, in Benishangul Gumuz Regional State (BGRS). TBISF project has led to the relocation of more than 300 people in Bambajihua site only since 2004 E.C. This study employed qualitative research method and a case study design. In-depth interviews with purposively selected eight dislocated individuals, two focus group discussions, and four key informant interviews with experts were conducted. The data was thematically analyzed. The findings showed that the dislocation process was highly chaotic. The dislocated people were forced to leave their residence in short notice and with no house constructed in the new site.  People were forced to reside in trees till they build their shelter. Neither the government personnels nor the sugar factory project coordinators assisted the dislocated community in transporting their materials to the new settlement site. During their arrival in the new residence, the reception they got from the local administration and the host community was hardly welcoming. There were also inconsistencies and favortismin settling compensations. Worsenning the situation for the resettles, the host community was not willing to share its grazing land and water with them. .  The only social service organizations available in the relocation site were a school, a health centre, and a police office. However, the institutions were not well equipped with professionals and other basic utilities. Even though the TBSIF project promised to construct roads and to facilitate access to electricity in the new relocation site, it has been five years and the promises  remain unfulfilled. The dislocated people also complained about lack of response to their demand for a pace of worship.There is security problem in Bambajihua. Properties are stolen and conflicts are common between the host and dislocated communities. The survival strategies of dislocated people included renting farmland and grazing land from the host community, digging underground well for drinking water,  tolerating  differences and using traditional conflict resolution mechanisms, and renting of privately owned houses for spiritual purpose. The study implies the dislocated people should get proper attention from Tana Beles Integrated Sugar Factory project coordinators and humanitarian service providers. Large scale studies need to be conducted to assess the impact of development-induced dislocation upon the resettles and the host communities in rural settings.